Understanding DeFi through the lens of a production-network model - Jonathan Chiu; Thorsten V. Koeppl; Hanna Yu; Shengxing Zhang (Bank of Canada, 2023)
Decentralized finance (DeFi) is composed of a variety of heterogeneous sectors that are interconnected through an input-output network of its tokens. We first use a panel data set to empirically document the evolution of the DeFi network across its different sectors. Instead of looking at the misleading measure of total value locked, we then employ a standard, theoretical production-network model to measure the value added and service outputs of the different DeFi sectors. Finally, based on a calibrated version of our model, we study which factors drive DeFi token prices and predict the equilibrium effects when network interconnectedness increases.
Keywords: G; G2; 330; Digital currencies and fintech; Payment clearing and settlement systems